2017
DOI: 10.1002/humu.23213
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mutations ofFOXF1cause alveolar capillary dysplasia despite not being imprinted

Abstract: Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a rare cause of pulmonary hypertension in newborns. Maternally inherited point mutations in Forkhead Box F1 gene (FOXF1), deletions of the gene, or its long-range enhancers on the maternal allele are responsible for this neonatal lethal disorder. Here, we describe monozygotic twins and one full-term newborn with ACD and gastrointestinal malformations caused by de novo mutations of FOXF1 on the maternal-inherited alleles. Since this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recently, based on qRT-PCR and bisulfite-PCR, Alsina Casanova et al [42] concluded that there was no evidence of imprinting at the 16q24.1 locus in lung tissue. However, due to a lack of informative SNVs, allelic expression of LINC01082 was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on qRT-PCR and bisulfite-PCR, Alsina Casanova et al [42] concluded that there was no evidence of imprinting at the 16q24.1 locus in lung tissue. However, due to a lack of informative SNVs, allelic expression of LINC01082 was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Unfortunately, detailed studies on imprinting of the FOXF1 locus in fetal, neonatal, and adult lung tissue have not been able to confirm this idea. 50 , 64 …”
Section: Imprinting Of Foxf1mentioning
confidence: 99%
“…Still, this might implicate parental imprinting of the regulatory region instead of the transcription region itself 49 . Unfortunately, detailed studies on imprinting of the FOXF1 locus in fetal, neonatal, and adult lung tissue have not been able to confirm this idea 50 , 64 …”
Section: Imprinting Of Foxf1mentioning
confidence: 99%
“…Of these, five parents were subsequently recognized as clinically affected ( FGFR3 , SCN5A X2, BAG3 and ENG ), with important implications for further cascade testing within the family; one parent was found to be mosaic ( SHH , 20% mosaicism). Parental transmission of FOXF1 and RANBP2 variants on the other hand, are thought to be explained by a parent-of-origin effect 16 and incomplete penetrance 17 , respectively. Eight individuals received a partial diagnosis, whereas another five had a dual diagnosis (Supplementary Tables 1 – 3 ).…”
Section: Resultsmentioning
confidence: 99%